(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Introduction Traditional treatment monitoring often relies on subjective assessments and infrequent check-ins. This approach has limitations in providing a complete picture of a patient's response. However, the future is bright with the rise of quantitative treatment monitoring. This emerging field utilizes data and analytics to provide a more objective, continuous, and personalized approach to monitoring treatment effectiveness.